Mapping the Informed Consent Process for Left Ventricular Assist Devices. Issue 5 (September 2018) - Fedson, Savitri E.; MacKenzie, Kelly K.; Delgado, Estevan D.; Abraham, Mackenzie N.; Estep, Jerry D.; Blumenthal-Barby, Jennifer S.; Bruce, Courtenay R.
Abstract : Ethical, practical, and medical challenges affect decisions about left ventricular assist device (LVAD) implantation. The informed consent document (IC-Doc) is integral to the decision-making process and structures informed consent conversations. The objective of this study was to analyze IC-Docs to identify the information patients and their families receive about LVAD implantation to create a model IC-Doc. We requested IC-Doc for LVAD implantation from LVAD programs in the United States. We analyzed them in three areas: medical and technical content, patient knowledge gaps, and syntax. Nineteen IC-Docs representing all United Network of Organ Sharing regions were included. Seventeen (89.5%) mentioned the indications for LVAD implantation (bridge to transplant or destination therapy), and six indicated which category applied to the patient. Palliative care was mentioned as an alternative in nine (47.4%); no IC-Doc discussed nonsurgical palliative care. Eight forms (42.1%) specifically mentioned turning off the LVAD. Eighteen forms mention general bleeding, and four referred to long-term gastrointestinal bleeding. Two IC-Docs addressed driveline infections. One form was written at an 8th grade reading level. There is wide variation in LVAD IC-Docs and omission of some benefits and risks. We have written an IC-Doc that meets criteria for disclosure, fills many knowledge gaps, and has an acceptable readability score. Abstract : Supplemental Digital Content is available in the text.